I foresee my life : the ritual performance of autobiography in an Amazonian community - Oakdale, Suzanne (University of Nebraska Press, 2005)
I Foresee My Life is a study of the ritual performances of the Kayabi, a Brazilian indigenous people, during the 1990s. Kayabi rituals are distinct in that they center on the autobiographical narratives of living people. Suzanne Oakdale discusses these autobiographical performances in the context of shamanic cures, mortuary rites, and political oratory. In each ritual, leaders describe how some of the dramatic environmental, economic, and political changes taking place in the Amazon have affected them. For example, the Kayabi have moved from a heavily colonized area to a reservation and as a result have had to address different facets of Indian identity, new forms of commodity consumption, residence patterns, and leadership.